2011
DOI: 10.1111/j.1365-2095.2011.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of dietary l-carnitine supplementation on diploid and triploid rainbow trout (Oncorhynchus mykiss)

Abstract: This study compared the effects of dietary l‐carnitine and ploidy on growth performances and fatty acid content in rainbow trout (Oncorhynchus mykiss). Fish [initial body weight (BW) = 30 g] reared under high density (50 kg biomass m−3) were hand‐fed in triplicate (3 tanks treatment−1, 34 fish tank−1) twice a day, with three nutritionally identical diets containing 15, 200 or 530 mg l‐carnitine kg−1 of diet. No significant growth differences were observed over a 56‐day grow‐out period, during which BWs increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 84 publications
(115 reference statements)
3
19
0
Order By: Relevance
“…Moreover, higher percentage of EPA and DHA in mature diploids compared to that of triploids, found by other authors (Flajshans et al, 2010;Ozorio et al, 2012;Manor et al, 2012Manor et al, , 2014Ribeiro et al, 2012), was confirmed in our study. It should be emphasized, that immature diploid fish did not differ significantly from triploids concerning EPA and DHA percentage.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Moreover, higher percentage of EPA and DHA in mature diploids compared to that of triploids, found by other authors (Flajshans et al, 2010;Ozorio et al, 2012;Manor et al, 2012Manor et al, , 2014Ribeiro et al, 2012), was confirmed in our study. It should be emphasized, that immature diploid fish did not differ significantly from triploids concerning EPA and DHA percentage.…”
Section: Discussionsupporting
confidence: 79%
“…It is important to note, that All the above data on less PUFA in triploids were based on measurements of their percentages in total fatty acids (Flajshans et al, 2010;Ozorio et al, 2012;64 65 Manor et al, 201264 65 Manor et al, , 2014Ribeiro et al, 2012). Meanwhile, it was demonstrated, that to for estimation of nutritive value for humans, measurements of PUFA per mass of consumed filets, rather than their percentage in total fatty acids should be carried out (Gladyshev, Sushchik, Gubanenko, Demirchieva, & Kalachova, 2007;Gladyshev et al, 2012;Huynh& Kitts, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…) and fatty acid metabolism (Ozório et al . ; Manor et al . ), suggesting differences in lipid utilization between diploids and triploids that precede, but continue through, energy investment into gonadal development.…”
Section: Discussionmentioning
confidence: 99%